Experimental study of soil anisotropy using hollow cylinder testing - Yang, Lintao (2013)
Most sedimentary deposits are inherently anisotropic due to their natural deposition in horizontal layers. This inherent anisotropy highlights the fact that the response of soils to loading is depending on both stress magnitude and its direction. Most of the field problems in geotechnical engineering are three-dimensional, and a soil is more likely to subject an anisotropic stress state (σ1 ≠ σ2 ≠ σ3), together with rotation of the principal axes. It is therefore essential that the soil behaviour under such realistic and general loading conditions is to be well understood, so that engineers can devise appropriate geotechnical design and analysis in practical situations.